INNOVATIVE TECHNOLOGIES IN THE NON-FERROUS METALLURGY OF UKRAINE – FLUORAMMONIUM TECHNOLOGY FOR THE DISCOVERY OF ILMENITE - Bazhenov, Yevgeny; Skachkov, Viktor; Metelenko, Natalya; Volyar, Roman; Skidin, Pavlo (Scientific Journal "Metallurgy", 2024)
The article is devoted to the generalization of the objective prerequisites of interest in titanium metal, which represents a unique combination of physical and chemical properties with significant earthly resources of titanium raw materials. The technical and economic criteria determining the rate of spread of titanium metal in innovative technologies of non-ferrous metallurgy, in particular, energy efficiency and environmental friendliness, have been updated. A critical analysis of modern technologies for obtaining titanium metal has been made, which includes the identification of problems in the technology for obtaining and further use of titanium metal; analysis of technologies for obtaining metal and derivatives based on it, which, in aggregate, combine technologies for cleaning intermediate materials; assessment of the shortcomings of chlorine technology along with its dominance in the world. The relevance of the transition from extensive efforts to revolutionary solutions for the development of technology for obtaining titanium metal has been outlined in order to solve the triune scientific task «optimization of costs for raw materials – energy efficiency – environmental conditioning of production». An initial assessment of the fluoroammonium technology for the opening of ilmenite in the production of titanium and titanium-containing materials has been made, the evolutionary path of the technology’s development has been investigated, and the prospects for its development has been outlined. The principal scheme of obtaining titanium dioxide by the technology of fluoroammonium opening of ilmenite concentrate with subsequent separation of the target components has been substantiated. The advantages and prospects of the technological solution of the proposed method of opening the ilmenite concentrate and subsequent separation of the target components to obtain titanium dioxide and iron oxide has been outlined. It has been proven that the technical and economic potential of the proposed conceptual solution is enhanced due to the possibility of obtaining silicon-containing components with the prospect of obtaining silicon dioxide of high purity. The results of laboratory research towards the development of technology for the separation of works on the isolation of siliconand titanium-containing components have been proven.